My Bunkmate Hates Puppies - Hay, Sam (Los Angeles : DisneyHyperion, 2023)
At her father's summer camp set in the middle of an enchanted forest, Bloom finds herself bunking with Cruella de Vil, who hates puppies (and pretty much everything else), and who wants to steal the rare furry Nerbit and turn it into a fancy hat.
Ages 6-8.
Grades 1-3.
Keywords: Magic -- Juvenile fiction; Camps -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Theft -- Juvenile fiction; Magic -- Fiction; Camps -- Fiction; Mythical animals -- Fiction; Stealing -- Fiction